Magnificent Monarchs - Glaser, Linda; Holland, Gay W. (Brookfield, Conn. : Millbrook Press, 2000)
Describes, in simple text and illustrations, the physical characteristics, habits, and life cycle of the monarch butterfly.
Keywords: Monarch butterfly -- Juvenile literature; Monarch butterfly; Butterflies